Psychological morbidity post miscarriage : a questionnaire based study among women in Hospital Tengku Ampuan Afzan, Kuantan - Lakshmi Paramananda (Kulliyyah of Medicine, International Islamic University Malaysia, 2014)
This study was conducted to determine the psychological outcomes following miscarriage up to 3 months in patients who sought treatment in Hospital Tengku Ampuan Afzan and to identify risk factors related to it. A cross-sectional study was designed involving the patients who were seeking treatment for miscarriage at our centre. The study comprised of a combination of a self-filled written questionnaire the General Health Questionnaire 12 (GHQ12) and Depression Anxiety Stress Scales 21 (DASS 21) immediately and 3 months post miscarriage after getting informed consent. Patients who fulfilled the inclusion criteria as stated below were eligible to participate in the study. Data was analyzed using IBM (SPSS) version 16.0 and a [p] value of < 0.05 was considered statistically significant. Chi-square and sample ʻtʼ test was also used to determine the socio-demographic characteristics and psychological morbidities. Among 150 women, using the General Health Questionnaire (GHQ 12) 24.7% of respondents had some psychological distress just after miscarriage and the incidence came down to 8% 3 months after the miscarriage. Using the DASS 21 questionnaire, overall there were about 28.7% of respondents who had psychological morbidity immediately after the miscarriage. These include depression (16.7%), anxiety (26.7%) and stress (6%) symptoms. After 3 months of miscarriage it was seen that the overall percentage came down to 11.3%. The risk factors associated to women who were prone to psychological distress were history of previous miscarriage, history of infertility, assisted conception and older age group. Our study showed that even after 3 months post miscarriage, some of these women were still affected psychologically. However the prevalence of distress reduced over time. Women who are at risk should be identified and followed up by the gynaecologist and referred appropriately.